2012
DOI: 10.1007/s11695-012-0658-4
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Swallow Study Following Bariatric Surgery: Institutional Review and Review of the Literature

Abstract: The results of our study show that a positive UGI study for stricture has a specificity of 100 %. In terms of leak, which offers a much higher risk of significant morbidity and mortality, UGI was unable to find any on postoperative days 1 or 2. Based on the results of this study, our institution has stopped completing routine UGI on POD 1 following bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…A limited number of studies have evaluated the usefulness of routine UGI contrast studies on postoper ative day 1 (POD 1) after LSG. Studies conducted in the United States, 18 Europe, 19 Eygpt 20 and the Middle East 21 have reported low sensitivity of the test. We have not iden tified any Canadian studies that investigated the utility and costeffectiveness of routine UGI contrast after LSG.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A limited number of studies have evaluated the usefulness of routine UGI contrast studies on postoper ative day 1 (POD 1) after LSG. Studies conducted in the United States, 18 Europe, 19 Eygpt 20 and the Middle East 21 have reported low sensitivity of the test. We have not iden tified any Canadian studies that investigated the utility and costeffectiveness of routine UGI contrast after LSG.…”
Section: Discussionmentioning
confidence: 98%
“…17 Comparing our study results to those of other published studies that evaluated the usefulness of routine contrast studies after LSGs, we find similar results in that most authors have not found routine contrast studies on POD 1 useful in detecting staple line leaks. The sensitivities quoted are consist ent with the results of the present study and, as in our study, most leaks were detected on CT. [18][19][20][21] In contrast, there is 1 small study from Greece that looked at routine Gastrografin swallows after LSG on POD 3. That study found that all leaks (3 of 85) were detected by the contrast studies 28 and con cluded that the routine contrast studies were indeed useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die Mehrzahl anderer Autoren kommt in ihren aktuell publizierten Arbeiten zu vergleichbaren Ergebnissen [5,7,14,25,27,28] Eine intraoperative Dichtigkeitskontrolle durch Luftinsufflation über eine Magensonde, Instillation von Blaulösung als sog. Blauprobe oder wie im eigenen Vorgehen die routinemäßige intraoperative Gastroskopie wird von vielen Adipositaschirurgen regelhaft durchgeführt [16].…”
Section: Niedrige Sensitivität Der Frühpostoperativen Routinemäßigen unclassified